Derivation of the Mathematical Approach to the Radial Pump's Meridional Channel Design Based on the Controlment of the Medial Axis. (19th October 2017) - Lu, Yeming; Wang, Xiaofang; Xie, Rong
Abstract : The meridional channel is the base for designing the radial pumps, and a new design approach is proposed here. Different from the previous studies, research here tries to establish the design model simply controlled with the radial coordinate. With the combination of a series of mathematical equations, the new design approach can shape the meridional contours directly by using the initial design variables. As for the mathematical constraint in the new design approach, it was presented in two forms, and each form had its corresponding solution. For the first form ( Constraint I ), the midpoints of the design points on the hub and shroud contours were thought to be located on the medial axis, and the PSO algorithm was adopted to search for the suitable results. Continually, to accelerate the design process, the second form ( Constraint II ) to simplify the mathematical constraint was added, and the explicit mathematical expressions calculating the coordinates on the hub and shroud contours were deduced. Finally, to check out the feasibility of the design approach in engineering, it was applied to redesign some typical meridional channels proposed by previous studies, and, through comparative analysis, the effectiveness of the new approach was evaluated and demonstrated.